2021
DOI: 10.1088/1361-6528/ac1d75
|View full text |Cite
|
Sign up to set email alerts
|

A review of focused ion beam applications in optical fibers

Abstract: Focused ion beam (FIB) technology has become a promising technique in micro-and nano-prototyping due to several advantages over its counterparts such as direct (maskless) processing, sub-10nm feature size, and high reproducibility. Moreover, FIB machining can be effectively implemented on both conventional planar substrates and unconventional curved surfaces such as optical fibers, which are popular as an effective medium for telecommunications. Optical fibers have also been widely used as intrinsically light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 212 publications
(481 reference statements)
0
16
0
Order By: Relevance
“…Several other studies reported for the microcantilever sensor [42], optical fiber-based tweezer [43], fiber microlens [44] etc. [45] have used FIB milling. Additionally, in terms of advanced LOF technology, Principe et al reported a novel integration of phase-gradient plasmonic metasurfaces over the optical fiber tip, named as optical fiber meta-tip, using FIB technology [46].…”
Section: Focused Ion Beam (Fib) Millingmentioning
confidence: 99%
“…Several other studies reported for the microcantilever sensor [42], optical fiber-based tweezer [43], fiber microlens [44] etc. [45] have used FIB milling. Additionally, in terms of advanced LOF technology, Principe et al reported a novel integration of phase-gradient plasmonic metasurfaces over the optical fiber tip, named as optical fiber meta-tip, using FIB technology [46].…”
Section: Focused Ion Beam (Fib) Millingmentioning
confidence: 99%
“…IB techniques, including ion implantation, irradiation, and focused IB (FIB) processing, have been extensively used to modulate the properties of nanomaterials. [ 154,155 ] Ion implantation and irradiation correspond to the continuous interaction between implanted ions and atoms and electrons in polymers, which leads to degradation, crosslinking, and degradation of small molecules, thereby enabling the processing of devices. [ 156,157 ] FIB is more commonly applied in micro‐ and nanofabrication, either through lithography, milling, or induced processing (e.g., deposition and etching), which involves material removal from the substrate and material addition.…”
Section: High‐energy Beam Processingmentioning
confidence: 99%
“…Only a few reviews related to ion beam technology including ion beam implantation and irradiation for surface modification/embedded nanostructures are reported for other applications such as fluorescence and optical imaging/ sensing, exhibiting their potential applications in SERS sensing. [22][23][24][25][26][27] However, there is no such detailed study reported on low energy ion beam technology (implantation or irradiation) based fabrication of SERS substrates.…”
Section: Introductionmentioning
confidence: 99%